Functional guild complementarity and morphological filtering in Annonaceae seed dispersal within a managed tropical garden - TRI HANDAYANI; HARY WAWANGNINGRUM; MUHAMMAD EFENDI; YUZAMMI YUZAMMI; TITUT YULISTYARINI (Nusantara Bioscience, 2026)
Abstract. Handayani T, Wawangningrum H, Yuzammi, Efendi M, Yulistyarini T. 2026. Functional guild complementarity and morphological filtering in Annonaceae seed dispersal within a managed tropical garden. Nusantara Bioscience 18 (1): n180103. https://doi.org/10.13057/nusbiosci/n180103. Understanding the mechanisms that structure plant-frugivore interactions in managed ex situ environments is essential for maintaining Seed Dispersal Effectiveness (SDE), genetic diversity, and long-term plant persistence. This study assessed the possible morphological filtering effect of Annonaceae fruit and seed traits on four co-existing frugivore guilds (birds, bats, squirrels, and civets) in the protected environment of the Bogor Botanical Gardens (BBG), Indonesia. To ensure a comprehensive dataset, we performed detailed morphological measurements and conducted twice-weekly observations across 22 Annonaceae species to identify fruit consumption patterns. We recorded fruit color, size, and shape, and statistically tested the classical morphological filtering hypothesis using Chi-Square, ANOVA, and Spearman correlation analyses. Our results showed a generally generalist interaction system, with the apocarpous fruit type being the most prevalent (12 species). The morphological specialization hypothesis was rejected, as fruit and seed size dimensions did not significantly correlate with specific visitor guilds (χ² = 9.793, df = 18, P = 0.938). Spearman’s rank correlation confirmed strong internal morphological constraints within the fruit (ρ > 0.70, P < 0.05), while no external ecological filtering regarding animal attraction was detected (ρ > 0.70, P > 0.05). This pattern indicates that frugivores in these managed collections exhibit high behavioral flexibility, utilizing a broad range of resources regardless of specific morphological traits. Despite this lack of strict matching, SDE is maintained through functional guild complementarity: bats act as long-distance dispersal specialists, while civets provide niche coverage for the largest fruits. However, the aggregated seed clumps deposited by civets remain a concern for recruitment. These findings show that generalist interactions, supported by complementary guild functions, underpin effective seed dispersal. Conserving the full frugivore assemblage is therefore critical to sustaining ecological processes in botanical gardens and should directly inform faunal management strategies.